Fertility after synchronization of estrus in dairy heifers using GnRH, PGF2a, and Progesterone (CIDR) - Richardson, A.M.; Hensley, B.A.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our objective was to determine fertility of heifers after synchronization of estrus using PGF2", preceded by progesterone, GnRH, or both. Dairy heifers (n = 246) were assigned randomly to three treatments: 1) 50 :g of GnRH given 6 d before 25 mg of PGF2 (d –1) plus a used intravaginal progesteronereleasing insert (CIDR-B; d –7 to 0; CIDR+GnRH); 2) same as CIDR+GnRH without the GnRH (CIDR); and 3) same as CIDR+GnRH without the used CIDR (GnRH). All heifers were fitted with Heat- Watch® patches and characteristics of estrus examined before AI included duration of estrus, number of standing events, and total duration of standing events. In addition, all heifers were observed visually twice daily for estrus. Rates of conception and pregnancy differed among treatments. All of the estrus-synchronization treatments produced acceptable estrus detection and pregnancy rates but the CIDR+PGF2" treatment was most effective for improving conception and pregnancy rates.
Keywords: Dairy; Estrus; Heifers; CIDR-B; Fertility